1992
DOI: 10.1093/nar/20.21.5527
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response of cloned DNA β-polymerase promoter is blocked in mutant cell lines deficient in protein kinase A

Abstract: DNA beta-polymerase (beta-pol), one of the recognized DNA polymerizing enzymes in vertebrates, has a role in 'very short patch' gap-filling synthesis during nucleotide excision DNA repair. In human and mouse, the enzyme is encoded by a single-copy gene located on the short arm of chromosome 8 near the centromere. In a series of studies, we have found that the cloned human beta-pol promoter is regulated by signals acting through the single ATF/CRE palindrome in the core promoter. These signals include transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…Previous studies have shown that the PKA signal transduction pathway is required for MNNG-induced ␤-pol promoter up-regulation (14,15) and that PKA phosphorylates CREB-1 at Ser 133 (23). In the present study, we examined whether the increased CREB-1 phosphorylation after MNNG treatment (Fig.…”
Section: Recruitment Of Closed Preinitiation Complex Is Stimulated Bymentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that the PKA signal transduction pathway is required for MNNG-induced ␤-pol promoter up-regulation (14,15) and that PKA phosphorylates CREB-1 at Ser 133 (23). In the present study, we examined whether the increased CREB-1 phosphorylation after MNNG treatment (Fig.…”
Section: Recruitment Of Closed Preinitiation Complex Is Stimulated Bymentioning
confidence: 86%
“…This induction required transcription (12), and use of a transfected ␤-pol core promoter fusion gene revealed transcriptional up-regulation of the ␤-pol promoter after MNNG treatment. This response is mediated through the CRE of the ␤-pol promoter (13), and up-regulation of promoter activity is dependent upon the protein kinase A (PKA) signal transduction pathway (14,15).…”
mentioning
confidence: 99%
“…In PKA lacking cells MNNG failed to activate the polβ promoter (29). PKA comprises of two catalytic (C) subunits and two regulatory (R) subunits (30).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activation of polβ promoter is exhibited strongly by DNA damaging agent MNNG treatment of CHO cells (33,34). Mutated polβ promotor fusion genes lacking the element failed to bind protein at this site and failed to respond to MNNG treatment of cells (29). It was shown that the Ser133 phosphorylated CRE binding protein (CREB) was higher versus control in vero cells after 60 min of MNNG treatment (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although a ras-dependent phosphorylation of ATF/CREB proteins has not yet been demonstrated, evidence suggesting ATF/CREB responsiveness to p21 r,s has been presented (Kedar et al, 1990;Galien et al, 1991). ATFs/CREBs proteins are a multigene family of transcriptional transactivators that provide trans-criptionally productive interactions when bound to the CREs of gene promoters, and whose binding and/or transcriptional activation functions are modulated by phosphorylations catalysed predominantly by cAMPdependent PKA (Habener, 1990;Englander & Wilson, 1992;de Groot & Sassone-Corsi, 1993;Masson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%